2017
DOI: 10.1128/jvi.02367-16
|View full text |Cite
|
Sign up to set email alerts
|

Azacytidine Treatment Inhibits the Progression of Herpes Stromal Keratitis by Enhancing Regulatory T Cell Function

Abstract: Ocular infection with herpes simplex virus 1 (HSV-1) sets off an inflammatory reaction in the cornea which leads to both virus clearance and chronic lesions that are orchestrated by CD4 T cells. Approaches that enhance the function of regulatory T cells (Treg) and dampen effector T cells can be effective to limit stromal keratitis (SK) lesion severity. In this report, we explore the novel approach of inhibiting DNA methyltransferase activity using 5-azacytidine (Aza; a cytosine analog) to limit HSV-1-induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 64 publications
0
45
0
Order By: Relevance
“…Approaches under consideration include agents that cause demethylation of the TSDR region of the FoxP3 gene such as Azacytidine, which was investigated for its effects on SK lesion severity (41). The results showed that Azacytidine therapy after disease process had been initiated effectively diminished lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches under consideration include agents that cause demethylation of the TSDR region of the FoxP3 gene such as Azacytidine, which was investigated for its effects on SK lesion severity (41). The results showed that Azacytidine therapy after disease process had been initiated effectively diminished lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were scarified on cornea with a 27-gauge needle, and a 3 µl drop containing 1×10 4 PFU of HSV-1 was applied to the eye. The eyes were examined on different days post infection (dpi) with a slit-lamp biomicroscope (Kowa Company, Nagoya, Japan), and the clinical severity of keratitis of individually scored mice was recorded as previously described (18). Briefly, the scoring system was as follows: 0, normal cornea; +1, mild corneal haze; +2, moderate corneal opacity or scarring; +3, severe corneal opacity but iris visible; +4, opaque cornea and corneal ulcer; +5, corneal rupture and necrotizing keratitis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, epigenetic modifiers such as HDACs or DNA methyltransferases (DNMTs) inhibitors are used. The use of azacytidine that inhibits DNMTs activity ameliorated herpes simplex virus 1 (HSV-1) induced ocular inflammatory lesion and enhanced Treg responses (81). …”
Section: How Do We Study the Function And Phenotype Of Treg And Th17 mentioning
confidence: 99%